Penerapan Pembelajaran Berbasis Metode Discovery Learning pada Mata Pelajaran Sejarah Kebudayaan Islam di MTs NUTirto Pekalongan - Akmal, Failasuf; Prayogi, Arditya; Mustika Sari, Nurul Husnah (Universitas Banda Naira, 2024)
Learning the history of Islamic culture, which is identical to the lecture method of learning, is still often carried out by teachers of the history of Islamic culture. In general, learning is still centered on the teacher, which causes students to quickly feel bored when listening, observing and working on questions from the teacher. Therefore, teachers must provide variations in using learning models, one of which is by implementing the discovery learning model which requires students to be active in learning, where this model has the aim of guiding students so that they can find the learning concepts they want for themselves. This article aims to describe the application of discovery learning in Islamic cultural history subjects at MTs NU Tirto Pekalongan, as well as to describe the supporting and inhibiting factors in its application. Based on the results of the study, an overview of the application of learning based on the discovery learning method in Islamic cultural history subjects at MTs NU Tirto Pekalongan was obtained, consisting of four stages, namely: First, planning which is the main description of a teacher in achieving learning objectives. Second, implementation which is an overall picture of when learning takes place, Third, evaluation is a systematic process to determine the effectiveness of the discovery learning learning model, Fourth, monitoring and adjustment by the teacher ensuring that learning takes place in accordance with the needs of students or not. Furthermore, in its implementation the supporting factors are adequate facilities and training or discussion space at MTs NU Tirto Pekalongan. Meanwhile, the inhibiting factors include lack of time, lack of student ability, and lack of interest in learning